Application of Microcontroller-Based Multipath Servos in Industrial Robot Control Systems - Ruiming Hu (Journal of Robotics)
In recent years, nanotechnology has continued to develop, especially the use of nanomaterials in various fields. Microcontroller is the most typical embedded system at this stage. With the development of science and technology, microcontroller has been widely used in people’s production life. A simple and practical multiservo controller can be built by using microcontroller and LED control chip PCA9685, which can realize at least 16 channels of servo control. In this paper, the control program of multichannel actuator is designed in detail, and the speed regulation of multichannel actuator is studied, which is applied to the industrial robot system driven by actuator. Nanomaterials, as new materials with various unique properties, have great application prospects, and this paper investigates the extension of nanomaterials in the field of robotic systems.